Hydroxystilbene Glucosides Are Incorporated into Norway Spruce Bark Lignin. Issue 3 (25th April 2019) - Rencoret, Jorge; Neiva, Duarte; Marques, Gisela; Gutiérrez, Ana; Kim, Hoon; Gominho, Jorge; Pereira, Helena; Ralph, John; del Río, José C.
Abstract : Hydroxystilbene glucosides, particularly isorhapontin and astringin, are incorporated into Norway spruce bark lignin and participate in radical coupling reactions during lignification. Abstract: Recent investigations have revealed that, in addition to monolignols, some phenolic compounds derived from the flavonoid and hydroxystilbene biosynthetic pathways can also function as true lignin monomers in some plants. In this study, we found that the hydroxystilbene glucosides isorhapontin (isorhapontigenin- O -glucoside) and, at lower levels, astringin (piceatannol- O -glucoside) and piceid (resveratrol- O -glucoside) are incorporated into the lignin polymer in Norway spruce ( Picea abies ) bark. The corresponding aglycones isorhapontigenin, piceatannol, and resveratrol, along with glucose, were released by derivatization followed by reductive cleavage, a chemical degradative method that cleaves β-ether bonds in lignin, indicating that the hydroxystilbene glucosides are (partially) incorporated into the lignin structure through β-ether bonds. Two-dimensional NMR analysis confirmed the occurrence of hydroxystilbene glucosides in this lignin, and provided additional information regarding their modes of incorporation into the polymer. The hydroxystilbene glucosides, particularly isorhapontin and astringin, can therefore be considered genuine lignin monomers that participate in coupling and cross-coupling reactions during lignification in Norway spruce bark.